25 kHz amorphous core transformer for induction heating applications - Lupi, S.; Fernandes Nunes, M. [UNESP] (Elsevier B.V., 1990)
The analysis of the feasibility and economics of amorphous core power transformers for induction heating applications in the field 10-50 kHz is developped. The results obtained on a 25 kHz-150 kVA concentric winding trial unit are presented. © 1990.
Keywords: Electric Heating, Induction; Iron and Alloys--Amorphous; Magnetic Cores--Materials; Amorphous Core Transformers; Flux Density; Electric Transformers